Respostas agudas ao exercício realizado em ergômetro de braço no sistema cardiovascular de pacientes com doença arterial periférica: ensaio crossover randomizado - Silva, Gustavo Oliveira da (2024)
INTRODUCTION: Peripheral artery disease (PAD) patients exhibit high risk of cardiovascular events. Strategies to decrease this risk are necessary. Arm-cranking (AC) training leads to benefits in the functional capacity of these patients, circumventing pain, but the cardiovascular responses to this exercise are still not clear. AIM: To analyse the acute cardiovascular responses to AC exercise in PAD patients, comparing it to walking exercise. METHODS: Randomized crossover trial in which fifteen PAD patients with intermittent claudication (53% men, 65±7 years, 26,7±4,7 kg/m2) performed three experimental conditions (Walking, AC and control) in random order. The exercise conditions were composed of 15×2 min with an intensity equivalent to 4-6 on Borg’s scale. We measured blood pressure (BP), cerebral blood flow, heart rate variability and brachial and femoral artery flow-mediated dilation (FMD) before and after the conditions (Post 10’ and Post 30’). Generalized estimated equations analysed the acute response among the experimental conditions, with P<0.05 considered significant. RESULTS: There were no significant baseline differences in cardiovascular variables (P>0.05 for all). Brachial and femoral artery FMDs did not significantly changed after any of the conditions (P>0.05 for all). Systolic BP progressively increased after the Control condition (Pre: 126±18mmHg, Post 10’: 138±17mmHg, and Post 30’: 146±20mmHg, P<0.05), while remained stable after the exercise conditions (P>0.05). Diastolic BP followed a similar pattern, increasing after the Control condition (Pre: 73±10mmHg, Post 10’: 77±9mmHg, Post 30’: 80±11mmHg, P<0.05), but remaining stable after the AC and Walking conditions (P>0.05). There were no significant changes on cerebral blood flow and heart rate variability (P>0.05 for all). CONCLUSION: A session of AC exercise attenuates the increase in BP observed in the absence of exercise in PAD patients, in a similar fashion to walking, without altering vascular function, cerebral blood flow and heart rate variability.